Peredaran Produk Kedaluwarsa dalam Parsel: Kajian Perlindungan Konsumen - Tahshinatus Salamah; Retno Catur Kusuma Dewi (SIGn Jurnal Hukum, 2023)
This study aims to examine and analyze the principles and legal forms of consumer protection against the circulation of expired products in parcels. This study uses normative legal research with the statute and comparative approaches. The collected legal material is then qualitatively analyzed to describe the problem and answer study purposes. The results show that the principles of consumer protection laws have become the primary focus of the global community. Furthermore, the principles and legal forms of consumer protection against the circulation of expired products in parcels encompass comprehensive policy-making, dispute resolution systems, information transparency, and consumer privacy protection. In addition, enhancing consumers’ knowledge, skills, and self-confidence in utilizing their rights to obtain compensation is a priority. Compliance by businesses with laws and responsive business practices also constitutes the principles and legal forms of consumer protection. Therefore, it is recommended that governments increase supervision against the circulation of expired products through stricter regulations and effective law enforcement while providing support for vulnerable and disadvantaged consumers. Businesses must ensure compliance with laws, regulations, and international consumer protection standards and implement clear and accessible product return, compensation, and replacement policies. Society, including consumers, must actively advocate and acquire the knowledge and skills to identify and avoid expired products in parcels. Finally, the collaboration between universities, businesses, and governments in researching and developing consumer protection policies related to expired products in parcels should be enhanced to generate innovative and effective solutions in the future.